The Influence of the Connections of Romanian Non-Listed Firms to Tax Havens on their Profitability - Mihai-Bogdan Afrasinei; Iuliana Eugenia Georgescu; Costel Istrate (CES Working Papers, 2016)
The offshore entities have become one of the most efficient solutions for tax avoidance and are used by taxpayers almost all around the world. This paper investigates the influence of the connections (via subsidiaries or shareholders) of Romanian non-listed firms to tax havens on their profitability and effective tax rate. In this regard, we used a sample of 7,167 Romanian firms (3,370 with connections to tax havens and 3,797 without tax havens connections). For statistical analysis, we used the simple and multiple linear regression methods with dummy variables. Results have shown that the presence of Romanian non-listed firms in tax havens significantly influences their profitability and effective tax rate. The firms with connections to tax havens have a return on equity ratio higher, a return on assets ratio lower, a gross profit margin ratio lower, a total assets turnover ratio higher and an effective tax rate lower than companies without connections to such jurisdictions
Keywords: F21; F23; M40; 330; tax havens; offshore companies; tax planning; tax optimization; tax avoidance; effective tax rate